Telemedicine, e-Health, and Digital Health Equity: A Scoping Review - Petretto, Donatella Rita; Carrogu, Gian Pietro; Gaviano, Luca; Berti, Roberta; Pinna, Martina; Petretto, Andrea Domenico; Pili, Roberto (Clinical practice and epidemiology in mental health, 2024)
With the progressive digitization of people's lives and in the specific healthcare context, the issue of equity in the healthcare domain has extended to digital environments or e-environments, assuming the connotation of "Digital Health Equity" (DHE). Telemedicine and e-Health, which represent the two main e-environments in the healthcare context, have shown great potential in the promotion of health outcomes, but there can be unintended consequences related to the risk of inequalities. In this paper, we aimed to review papers that have investigated the topic of Digital Health Equity in Telemedicine and e-Health [definition(s), advantages, barriers and risk factors, interventions]. We conducted a scoping review according to the methodological framework proposed in PRISMA-ScR guidelines on the relationship between Digital Health Equity and Telemedicine and e-Health Scopus and Pubmed electronic databases. The following inclusion criteria were established: papers on the relationship between Digital Health Equity and Telemedicine and/or e-Health, written in English, and having no time limits. All study designs were eligible, including those that have utilized qualitative and quantitative methods, methodology, or guidelines reports, except for meta-reviews. Regarding Digital Health Equity in Telemedicine and e-Health, even if there is no unique definition, there is a general agreement on the idea that it is a complex and multidimensional phenomenon. When promoting Digital Health Equity, some people may incur some risk/s of inequities and/or they may meet some obstacles. Regarding intervention, some authors have proposed a specific field/level of intervention, while other authors have discussed multidimensional interventions based on interdependence among the different levels and the mutually reinforcing effects between all of them. In summary, the present paper has discussed Digital Health Equity in Telemedicine and e-Health. Promoting equity of access to healthcare is a significant challenge in contemporary times and in the near future. While on the one hand, the construct "equity" applied to the health context highlights the importance of creating and sustaining the conditions to allow anyone to be able to reach (and develop) their "health potential", it also raises numerous questions on "how this can happen". An overall and integrated picture of all the variables that promote DHE is needed, taking into account the interdependence among the different levels and the mutually reinforcing effects between all of them.